Making films under Salazar’s gaze: Cinematic representation of Lisbon in two popular comedies of the 1940s - Brás, Rui Manuel (2012)
Lisbon was the setting for most of the comedies produced in Portugal during the 1940’s. This fact not only corroborates the notion of Lisbon as the head of the Empire, and the weight it had in administrative and political terms, but it also indicates that the city was the right stage for these comedies which, apparently, were filmed to be a mere vehicle of the state’s propaganda. The values of family and fatherland, the praise of simple life, honesty, and acceptance of the social hierarchy are dominant aspects of these films set in different parts of the city. For some scholars, however, Lisbon as a city in itself was not really present in these films, where the urban-rural dichotomy was underscored in order to favour the official ideology of the Estado Novo that considered with suspicion the urban forms of sociability. My contention in this paper is that the city was not always represented as an ideal(ized) closed space, in many ways similar to rural communities, but that it was the stage for the performance of acts that contradicted the official ideology through the use of metaphors, that the spaces produced in those films are unstable, and open to subversion. For that purpose, I will base my analysis on two of the most emblematic comedies of the 1940’s: O Pai Tirano (The Tyrant Father), by António Lopes Ribeiro, and O Pátio das Cantigas (The Courtyard of the Ballads), by Francisco Ribeiro.